ŚWIADCZENIA Z POMOCY SPOŁECZNEJ A OBOWIĄZKI ALIMENTACYJNE CZŁONKÓW RODZINY - Andrzejewski, Marek (Wydział Prawa i Administracji UAM, 1999)
The Author analyses decisions taken by social assistance institutions and respective appellate agencies; decisions issued by courts where an obligation to pay alimony was involved and, finally, utterances of the doctrine representatives in this matter. The Author is critical about presently preferred model o f social policy and about its practical functioning; respective legal regulations in the Constitutions from 1997 are also discussed as well as those in the law on social assistance (1990) and those comprised in presently in force Family and Guardianship Code. Also mutual relations between Polish law on alimony payment (and other laws concerning family matters) and the practice of social assistance are appreciated by the Author who is having, on this occasion, recourse to the examples of verdicts issued by the Supreme Court of the Republic o f Poland.
SOCIAL BENEFITS AND OBLIGATIONS OF MAINTENANCE AMONG FAMILY MEMBERS